2023
DOI: 10.1186/s13018-023-04001-2
|View full text |Cite|
|
Sign up to set email alerts
|

6 February 2023, orthopedic experience in Kahramanmaraş earthquake and surgical decision in patients with crush syndrome

Abstract: Background The decision of fasciotomy or amputation in crush syndrome is controversial and challenging for surgeons. We aimed to share our experiences after the Kahramanmaraş earthquake, to predict the severity of crush syndrome and mortality, and to guide the surgical decision. Methods The clinical data of patients during their first week of hospitalization were analyzed retrospectively. Totally, 233 crush syndrome patients were included. Demograp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In these types of injuries, the amputation rates vary between 3% and 58%. [10] In the study by Kundakcı et al, [17] patients with crush extremity injuries affected by the earthquake were examined and a relationship was found between peak CK level and amputation, but no difference was found in terms of the requirement for fasciotomy. In our study, the majority of crush injuries were mostly extremities injuries and 54.5% of the patients underwent procedures such as debridement, fasciotomy, and/or amputation of their extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these types of injuries, the amputation rates vary between 3% and 58%. [10] In the study by Kundakcı et al, [17] patients with crush extremity injuries affected by the earthquake were examined and a relationship was found between peak CK level and amputation, but no difference was found in terms of the requirement for fasciotomy. In our study, the majority of crush injuries were mostly extremities injuries and 54.5% of the patients underwent procedures such as debridement, fasciotomy, and/or amputation of their extremities.…”
Section: Discussionmentioning
confidence: 99%
“…[20] In crush injuries, the need for hemodialysis is usually temporary and but life-saving. [4,10,11] In a study by Kundakcı et al, [17] it was found that around 50% of patients with crush extremity injuries caused by an earthquake required hemodialysis. In our study, 32.1% of patients with crush injury needed hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Crush injuries occur as a result of direct trauma to the tissue and compression of the body in one place [ 2 ]. Edema resulting from bleeding and tissue damage may increase intracompartmental pressure, which can cause the development of compartment syndrome [ 16 ]. Compartment syndrome was observed in 38.7% of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Abrasions and necrotic wounds due to crushing are common. Antiseptics, debridement, and negative pressure wound therapy are the most commonly applied wound care methods ( 7 , 8 ).…”
Section: Case Reportsmentioning
confidence: 99%